CHARACTERIZATION OF LIPID FROM BLACK SOLDIER FLY LARVA GROWN ON OKARA - Majid, Zuliyan Agus Nur Muchlis; Arwani, Muhammad; Rohmanna, Novianti Adi; Deorato, Panji; Febrianto, Arie; Faradila, Rosevia Galuh; Khusumawati, Anggraeni Dwi (BPFP Faperta UNIB, 2026)
Okara is by-product of tofu production with a rich nutritional, mainly protein, lipid, and carbohydrate. Okara has the potential as diet food of black soldier fly larvae (BSFL). In addition to waste management, BSFL produce high-lipids biomass that could be used as biodiesel materials. This research used a lipid extraction process with a microwave-assisted extraction method. Through rearing BSFL on Okara, 100 BSFL were harvested at the 14 days old. It was found the BSF-derived oil biomass had 35.40% lipid content and 40.44% protein content. The response surface methodology investigated the effect of sample-to-solvent ratio (1:3.1 - 1:8.83 w/v %) and extraction time (11.7-68.3 min) for minimum FFA, Acid value, and maximum yield. The optimum lipid yield was conducted to the esterification and trans-esterification process with 0.05 % H2SO4 in 98 % methanol at 60˚C for 1 hour. The optimal combination of the analysis results obtained a sample-to-solvent ratio of 1:4 w/v and an extraction time of 60 minutes. The properties of BSF-derived oil biomass had 3.026% FFA, 6.004% Acid value, and 29.397% lipid yield. FAME from biodiesel derived from BSFl biomass was predominantly constitued about C12:0 at around 44.47%, followed by C18:2 at around 14.25%, and C16:0 at around 11.32%.